Evaluation of the logistics process of the Riobamba service company - Moreno Ayala, Jessica; Villacis Betancourt, Cristhian Andrés; Velasco Castelo, Geoconda; Villacis Betancourt, Julio Javier (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June), 2022)
The objective of this research is to evaluate the logistics process of the Servientrega company located in the city of Riobamba, province of Chimborazo. The development of the same has a qualitative and quantitative approach, through the application of surveys to identify the client's perception. Observation sheets were also used to determine the level of compliance with the parameters established in each of the logistics processes. The shortcomings that the company currently has were identified, among which the daily activities of the company can be mentioned, such as: conditions and forms of distribution and in the solution centers, delays in delivery, inadequate handling of the merchandise. The analysis and evaluation of the different stages of the logistics process of Servientrega will allow decisions to be made about the changes that can be made in the company, to make the process more efficient and reduce the costs of each stage.